Rapid resolution of colitis related to immunosuppressive medication after infliximab administration. (30th June 2020) - Coghill, Matthew; Howell, Mary; Wallis, Gonzalo; Dranove, Jason
Abstract: Immunosuppression is necessary after solid organ transplantation. The non‐infectious side effects associated with many of these agents are not well understood. We report a case of colitis, most resembling inflammatory bowel disease, that persisted despite withdrawal of tacrolimus and mycophenolate mofetil and transition to alternative agents. The patient was treated for clostridium difficile without improvement. Endoscopic biopsies demonstrated non‐specific inflammation without evidence of active infection. An extensive immunologic and oncologic workup was negative. Ultimately, we trialed the administration of infliximab, a monoclonal antibody that inhibits TNF‐alpha receptors that is commonly used in the treatment of inflammatory bowel disease. With infliximab treatment, the patient experienced rapid resolution of his disease and has remained in remission.